Pengembangan Flashcard pada Gamifikasi Pembelajaran Biologi Materi Ekosistem - Ulfa Ramadhani; Heffi Alberida (LP2M UIN Ambon, 2026)
Learning media serve as a means to facilitate the delivery of material so that the learning process can run optimally. However, their utilization is still limited in variation and interactivity, causing students to feel bored and less motivated to participate in learning, especially in complex topics such as ecosystems. This study aims to develop flashcard media in gamified biology learning on ecosystem material that are valid and practical. This research is categorized as development research using the 4-D model, which includes the stages of defining, designing, developing, and disseminating, but is limited to the development stage. The research subjects consisted of two expert lecturers, one biology teacher, and 34 Phase E students at MAN 1 Bungo. Data were collected through observation sheets, validity questionnaires, and practicality questionnaires, and then analyzed using descriptive techniques. The results indicate that the developed media achieved a validity score of 92.43% with a very valid category. The practicality score assessed by the teacher reached 93.54%, while the students’ assessment was 94.18%, both categorized as very practical. Therefore, the developed media is considered feasible to be used as an alternative in biology learning.